Pendidikan Ibu dan Ayah sebagai Determinan Stunting Balita pada Rumah Tangga Muslim di Indonesia - Tarissa Chairina Mirsal; Donny Hardiawan; Cupian (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2026)
Stunting among children under five years of age constitutes a chronic nutritional problem that remains a serious challenge in Indonesia, with a prevalence of 35.3% observed among Muslim households based on the fifth wave of the Indonesian Family Life Survey (IFLS). This research examines the relationship between parental education, religious participation, and the probability of stunting among children in Indonesian Muslim households. Binary logistic regression with a marginal effects approach was applied to a sample of 2,813 children aged 0–59 months from 2,558 Muslim households. Findings indicate that paternal education at the senior secondary and tertiary levels significantly reduces the probability of child stunting by 8.9 and 7.5 percentage points, respectively, while maternal education at the senior secondary level reduces the probability by 5.9 percentage points. Paternal participation in religious study gatherings (pengajian or majelis taklim) is significantly and negatively associated with stunting, suggesting that socio-religious spaces may reinforce nutritional awareness within families. Maternal religious participation, however, yields no statistically significant association. Household economic status and urban residence also contribute significantly to the probability of stunting. These findings affirm that stunting reduction interventions within Muslim communities should account for the educational roles of both parents and leverage religious forums as effective channels for nutritional education within the framework of human capital development from an Islamic economics perspective.